Nitrogen-fixing trees and soil macrofauna in Digitaria hybrid pasture - Dias, Paulo Francisco; Souto, Sebastião Manhães; Correia, Maria Elizabeth Fernandes; Rocha, Gudesteu Porto; Moreira, Joventino Fernandes; Rodrigues, Khalil de Menezes; Franco, Avílio Antônio (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of tree legume species on the density and diversity of macrofauna of a Red Yellow Argisol with low natural fertility. Two nitrogen-fixing trees, orelha-de-negro (Enterolobium contortisiliquum) and jacarandá-da-baía (Dalbergia nigra), and one non nitrogen-fixing tree, angico-canjiquinha (Peltophorum dubium), were intercropped with survenola grass (an interspecific hybrid of Digitaria setivalva and Digitaria valida), having pasture at full sun as control. Formicidae was the most abundant group, followed by Oligochaeta with 47% in the legume treatments and 23% in the pasture at full sun. The largest values for the fauna diversity were obtained in samplings under the canopy of nitrogen-fixing tree legumes. The cluster analysis showed that the intercropping with orelha-de-negro presented soil fauna groups quite similar to the ones under jacarandá-da-baía. According to the correspondence multivariate analysis, the tree legumes contributed to an increase in the density of some fauna groups, mainly Oligochaeta, Coleoptera, Araneae and Formicidae.